GRK2 differentially regulates FcεRI and MRGPRB2-mediated responses in mast cells - Thapaliya, Monica; Ali, Hydar (Frontiers in Immunology, 2023)
In addition to high-affinity IgE receptor (FcRI), a subtype of mouse mast cells (MCs) expresses a G protein-coupled receptor known as Mas-related G protein-coupled receptor (GPCR)-B2 (MRGPRB2; human ortholog MRGPRX2). GPCR kinase 2 (GRK2) is a Serine/Threonine kinase that phosphorylates GPCRs to promote their desensitization and internalization. We previously showed that silencing GRK2 expression in mouse bone marrow-derived MCs (BMMCs) blocks IgE-mediated degranulation. Compound 48/80 (C48/80), substance P (SP) and LL-37 cause degranulation in human and mouse MCs via MRGPRX2 and MRGPRB2, respectively. We also reported that C48/80 and SP cause desensitization and internalization of MRGPRX2, but LL-37 does not. Here, we generated mice with MC-specific deletion of Grk2 (Cpa3Cre+/Grk2fl/fl) to determine its role on IgE-mediated responses and to assess whether it differentially regulates degranulation in response to LL-37, C48/80 and SP. Absence of GRK2 substantially inhibited IgE-mediated tyrosine phosphorylation of STAT5, calcium mobilization, and degranulation in mouse primary lung-derived MCs (PLMCs). By contrast, peritoneal MCs (PMCs) from Cpa3Cre+/Grk2fl/fl mice demonstrated significant enhancement of degranulation in response to C48/80 and SP, but not LL-37. Deletion of Grk2 in MCs attenuated IgE-mediated passive cutaneous anaphylaxis (PCA) and itch but not passive systemic anaphylaxis (PSA). Surprisingly, PSA was significantly reduced in Mrgprb2-/- mice. These findings suggest that GRK2 contributes to PCA and itch but not PSA. By contrast, GRK2 desensitizes MRGPRX2/B2-mediated responses to C48/80 and SP but not LL-37. However, IgE-mediated PSA likely involves the activation of MRGPRB2 by LL-37 or a similar agonist, whose function is resistant to modulation by GRK2.